2018
DOI: 10.1038/s41467-018-03093-3
|View full text |Cite
|
Sign up to set email alerts
|

A light carbon isotope composition for the Sun

Abstract: Measurements by the Genesis mission have shown that solar wind oxygen is depleted in the rare isotopes, 17O and 18O, by approximately 80 and 100‰, respectively, relative to Earth’s oceans, with inferred photospheric values of about −60‰ for both isotopes. Direct astronomical measurements of CO absorption lines in the solar photosphere have previously yielded a wide range of O isotope ratios. Here, we reanalyze the line strengths for high-temperature rovibrational transitions in photospheric CO from ATMOS FTS d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 68 publications
7
30
0
Order By: Relevance
“…() would be −77‰, possibly acceptably close to Lyons et al. (). A Genesis solar wind 13 C/ 12 C measurement could distinguish between −77 and −48‰ and enable improved interpretations of lunar regolith C data.…”
Section: Future Opportunities In Genesis Sciencesupporting
confidence: 72%
See 1 more Smart Citation
“…() would be −77‰, possibly acceptably close to Lyons et al. (). A Genesis solar wind 13 C/ 12 C measurement could distinguish between −77 and −48‰ and enable improved interpretations of lunar regolith C data.…”
Section: Future Opportunities In Genesis Sciencesupporting
confidence: 72%
“…Based on solar CO absorption lines, and using data processing models that give δ 18 O of −50 ± 11‰ (1 sigma error) in agreement with Genesis, Lyons et al. () report solar δ 13 C = −48 ± 7‰. Using a rough estimate of the solar wind C fractionation of 28‰, the inferred solar C isotopic composition from Hashizumi et al.…”
Section: Future Opportunities In Genesis Sciencementioning
confidence: 78%
“…Hashizume et al (2004) argued on the basis of SIMS depth profile measurements of lunar soils that it is isotopically light relative to the Earth, with δ 13 C <-100 ‰. Recently, Lyons et al (2017) reported a spectroscopic measurement of CO in the solar photosphere, yielding δ 13 C = -48 ± 7‰. Thus, although the lunar measurement of Hashizume et al (2004) does not rule out as extreme a 13 C depletion in the Sun as observed in A7_60, the astronomical measurement argues against it.…”
Section: Organic Mattermentioning
confidence: 99%
“…The results reported by Fujiya et al 1 therefore raise many questions about the origin of isotopic variations, such as the role of photochemical processes in producing 13 Cenrichments 17 , and the general structure of the protoplanetary disk. Future comparison of the present data with samples of hydrated B-and C-type asteroids expected to be returned to Earth by the OSIRIS-REx and Hayabusa 2 missions will thus be fundamental to further quantifying large-scale pertubations in the early Solar Sytem.…”
Section: Yves Marrocchi and Laurette Pianimentioning
confidence: 98%